Cancer Cells Expressing Oncogenic Rat Sarcoma Show Drug-Addiction Toward Epidermal Growth Factor Receptor Antibodies Mediated by Sustained MAPK Signaling - Tintelnot, Joseph; Metz, Sina; Trentmann, Marie; Oberle, Anna; von Wenserski, Lisa; Schultheiß, Christoph; Braig, Friederike; Kriegs, Malte; Fehse, Boris; Riecken, Kristoffer; Bokemeyer, Carsten; Stein, Alexander; et al. (Frontiers in Oncology, 2020)
Epidermal growth factor receptor (EGFR) antibodies may have detrimental effects in patients with metastatic colorectal cancer expressing oncogenic Rat sarcoma (RAS). Since a significant number of patients acquire RAS-mediated resistance during EGFR-directed treatment, understanding the molecular mechanism underlying these antibody-mediated tumor-promoting effects is of relevance to design more resistance-preventive treatment approaches. To test this, we set up a Ba/F3 cellular model system transformed to EGFR/RAS dependency to be able to study proliferation, RAS activity as well as MAPK signaling upon inhibition of wild-type RAS isoforms by therapeutic EGFR antibodies. Here, we show that the EGFR antibodies cetuximab and panitumumab induce paradoxical stimulation and enhance proliferation in cells expressing oncogenic RAS (KRAS G12V). These experiments clearly showed that the stimulatory effect is a direct result of the antibody-EGFR interaction leading to prolonged mitogen-activated protein-Kinase (MAPK) signaling. The effect was also induced by antibody-chemotherapy combinations but always depended on simultaneous low-level ligand-dependent EGFR pathway activation. Moreover, we observed significant growth retardation of RAS mutant cells after antibody withdrawal compatible with a drug-addiction phenotype. Our data suggests that EGFR antibodies paradoxically sustain MAPK signaling downstream of oncogenic RAS thereby driving proliferation of RAS mutant tumors or tumor subclones. The observed drug-addiction encourages fixed-duration or liquid-biopsy-guided drug holiday concepts to preventively clear RAS mutant subclones selected under EGFR-directed therapeutic pressure.